Skogsbränsledrivare i klen förstagallring med contorta - Johansson, Patrik (2010)
The aim for the study was to examine a harwarder´s (combined harvester-forwarder) productivity when harvesting forest fuel in first thinning stands that contains Lodgepole pine and calculate the economy of the harvesting work and estimate the quality of the thinning . The field study area where located near Arvån, about 15 kilometres south –east from the city of Lycksele. The field studies were taken place in three different stands. All tree stands had the same tree age, but the tree species combination and the density varied. The harwarder in the study was a Valmet 801 combi modified for whole tree harvesting. Ten study units were created in the tree stands, each study unit was 1250 m2. The average density before thinning was 3809 trees/ha, the average stem size was 0.031 m3.